Agama dan Budaya Teras Masyarakat Madani - Bakar, Osman (Jurnal Usuluddin, 1997)
This paper discusses al-Farabi’s concept of civil society and two fundamental ideas that are closely related to it, namely the idea of man as a "political animal" and the importance of the science of civilisation. The paper also deals with al-Farabi’s philosophy of happiness and explains why religion must serve as the foundation of a civil society.